Dabigatran for the prevention and treatment of thromboembolic disorders. (May 2015) - Enriquez, Andres; Baranchuk, Adrian; Redfearn, Damian; Simpson, Christopher; Abdollah, Hoshiar; Michael, Kevin
<x xml:space="preserve">Abstract</x> Dabigatran, an oral direct thrombin inhibitor, was the first of a new class of drugs referred to as non-vitamin K oral anticoagulants. Dabigatran is better than warfarin for stroke prevention in non-valvular atrial fibrillation (dose of 150 mg twice a day), non-inferior to enoxaparin for venous thromboembolism prevention after orthopedic surgery and non-inferior to warfarin in preventing recurrence after acute venous thromboembolism. The safety profile is similar to standard anticoagulants, with significant reduction observed in intracranial hemorrhage. Other advantages include a rapid onset of action and a predictable pharmacokinetic profile, allowing a fixed-dose regimen without the need for routine anticoagulation monitoring. In the event of bleeding, general support measures are recommended and if severe, the use of non-specific hemostatic agents such as prothrombin complex concentrates and recombinant factor VIIa must be considered. A specific reversal agent (idarucizumab) is in development.